Elevated luteinizing hormone despite normal testosterone levels in older men—natural history, risk factors and clinical features. (25th December 2017) - Eendebak, Robert J. A. H.; Ahern, Tomas; Swiecicka, Agnieszka; Pye, Stephen R.; O'Neill, Terence W.; Bartfai, Gyorgy; Casanueva, Felipe F.; Maggi, Mario; Forti, Gianni; Giwercman, Aleksander; Han, Thang S.; Słowikowska‐Hilczer, Jolanta; et al.
Summary: Objective: Elevated luteinizing hormone (LH) with normal testosterone (T) suggests compensated dysregulation of the gonadal axis. We describe the natural history, risk factors and clinical parameters associated with the development of high LH (HLH, LH >9.4 U/L) in ageing men with normal T (T ≥ 10.5 nmol/L). Design, Patients and Measurements: We conducted a 4.3‐year prospective observational study of 3369 community‐dwelling European men aged 40‐79 years. Participants were classified as follows: incident (i) HLH (n = 101, 5.2%); persistent (p) HLH (n = 128, 6.6%); reverted (r) HLH (n = 46, 2.4%); or persistent normal LH (pNLH, n = 1667, 85.8%). Potential predictors and changes in clinical features associated with iHLH and rHLH were analysed using regression models. Results: Age >70 years (OR = 4.12 [2.07‐8.20]), diabetes (OR = 2.86 [1.42‐5.77]), chronic pain (OR = 2.53 [1.34‐4.77]), predegree education (OR = 1.79 [1.01‐3.20]) and low physical activity (PASE ≤ 78, OR = 2.37 [1.24‐4.50]) predicted development of HLH. Younger age (40‐49 years, OR = 8.14 [1.35‐49.13]) and nonsmoking (OR = 5.39 [1.48‐19.65]) predicted recovery from HLH. Men with iHLH developed erectile dysfunction, poor health, cardiovascular disease (CVD) and cancer more frequently than pNLH men. In pHLH men, comorbidities, including CVD, developed more frequently, and cognitive and physical function deteriorated more, than in pNLH men. Men with HLH developed primary hypogonadism more frequently (OR = 15.97 [5.85‐43.60]) than NLH men. Men with rHLH experienced a small rise in BMI. Conclusions: Elevation of LH with normal T is predicted by multiple factors, reverts frequently and is not associated with unequivocal evidence of androgen deficiency. High LH is a biomarker for deteriorating health in aged men who tend to develop primary hypogonadism.